2008
DOI: 10.3801/iafss.fss.9-1279
|View full text |Cite
|
Sign up to set email alerts
|

Fire behaviour of cross-laminated solid timber panels

Abstract: Cross-laminated solid timber panels represent an interesting technical and economical product for modern timber structures. The use of large prefabricated cross-laminated solid timber panels for load-bearing wall and floor assemblies has become increasingly popular in particular for residential timber buildings. The fire behaviour of cross-laminated solid timber panels has been experimentally and numerically studied during two different ongoing research projects carried out at the Institute of Structural Engin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 5 publications
1
35
0
4
Order By: Relevance
“…The significance of the char layer has been investigated in many tests with cross-laminated timber where char ablation (e.g. for fall-off of charred layers Cross-Laminated Timber) lead to a significantly increased charring rate (Frangi et al, 2008).…”
Section: Simulation Of Char Oxidationmentioning
confidence: 99%
“…The significance of the char layer has been investigated in many tests with cross-laminated timber where char ablation (e.g. for fall-off of charred layers Cross-Laminated Timber) lead to a significantly increased charring rate (Frangi et al, 2008).…”
Section: Simulation Of Char Oxidationmentioning
confidence: 99%
“…Panel yang disusun secara vertikal untuk stuktural, seperti dinding, lebih tahan api daripada yang dipasang horisontal, seperti lantai. Karakteristik penyebaran api pada bangunan CLT juga ditentukan oleh karakteristik dari masing-masing lapisan yang membentuk panel, apabila lapisan arang dari lamina yang terbakar lepas maka akan terjadi kenaikan kecepatan perambatan api pada lapisan yang belum terbakar dan hal ini juga terjadi pada material yang sudah diberi lapisan anti api, apabila lapisan anti api terlepas maka api akan lebih cepat merambat (Frangi, Fontana, Knobloch, & Bochicchio, 2008). Mekanisme anti api pada CLT berupa lapisan arang yang terbentuk dari bagian yang terbakar yang akan melindungi lapisan kayu di bawahnya yang belum terbakar, sehingga menjaga struktur bangunan tetap kuat dan tidak mengalami kerusakan (deformasi) sehingga mencegah bangunan untuk tidak runtuh dan memberi cukup waktu untuk evakuasi (Friquin, Grimsbu, & Hovde, 2010;Wong & Tee, 2014).…”
Section: Keunggulan Karakteristik Cltunclassified
“…Three-ply systems also place 66% of the timber in a 'strong' orientation, whereas as the number of plies increases the strong timber tends towards 50% of the cross-section. Frangi et al [15] have also suggested that using thicker external lamellae, and a 3-ply rather than 5-ply build up, can reduce the risk of delamination in fire and thereby reduce the effective charring rate for CLT products that are susceptible to delamination. These factors could result in designers concluding that 3-ply systems are preferred to 5-ply systems.…”
Section: Importance Of Clt Lay-upmentioning
confidence: 99%
“…It is noteworthy that delamination may also contribute additional fuel to a fire compartment, thus altering the resultant fire dynamics and further influencing the structural fire response (and fire resistance). While delamination has previously been reported as an important issue to consider for CLT floor slabs in fire [15,16], it has been suggested that it is less likely in furnace tests of vertically oriented elements, presumably due to reduced separation forces from gravity [17,18]. Delamination should not be confused with debonding, which describes loss of composite mechanical action between lamellae, with both plies still theoretically capable of performing a significant load bearing function [19].…”
Section: Fire-induced Delaminationmentioning
confidence: 99%
See 1 more Smart Citation